Potencializando o ensino de geometria com o uso do Origami modular e o software Poly Pro na construção dos sólidos de Platão - Flôres, Jozeane Candido Moreira (2023)
This research aimed to develop activities designed to enhance the learning of Platonic solids in spatial geometry. This was achieved using the Poly Pro mathematical software, version 1.12, along with modular origami. These activities were developed in a 2nd-year high school class in the city of Rio Crespo/RO. The theoretical foundation lies in Lev Vygotsky's socio-interactionist theory, particularly his concepts of mediation, zone of proximal development, and the construction of scientific concepts. The research was both quantitative and qualitative in nature and was guided by the following question: Can the use of modular origami and Poly Pro software aid the teaching process and, consequently, enhance the learning of spatial geometry in relation to Platonic solids? The objective was to provide conditions for teaching Platonic solids through the inclusion and practice of origami, along with the Poly Pro software, with the intention of enhancing the learning of this content. The methodology applied was carried out in three stages: 1st Conventional; 2nd Manipulative with Origami; and 3rd Use of Poly Pro software. Data collection instruments included questionnaires administered to students and records of the activities developed. To assist other teachers in carrying out similar actions, the Educational Product "Polygami: A proposal for teaching the Geometry of Platonic solids using Poly Pro software and Modular Origami" was developed, available on the PPGECM page https://www.upf.br/ppgecm/dissertacoes-e-teses and Educapes http://educapes.capes.gov.br/handle/capes/743171. This research concluded that modular origami and the Poly Pro software, when associated with the aforementioned activity, are powerful tools for learning the geometric concepts involved in Platonic solids. Furthermore, it revealed how the teacher is an active and transformative agent, responsible for enhancing the appropriation and use of tools and symbols by the research subjects.